2021
DOI: 10.9734/cjast/2021/v40i4831639
|View full text |Cite
|
Sign up to set email alerts
|

Status and Scenario of Genome Editing Device CRISPR-Cas9 in Crop Advancement

Abstract: Plant breeding systems have a extensive antiquity and they had been employed meanwhile the commencement of subjugation of the initial agricultural crop plants. Subsequently, innumerable novel procedures have and are being advanced to added upsurge the profitable worth and harvest of plants. The newest crop enhancement method recognized as genome editing is a method which empowers accurate alteration of the crop genome via bashing out unwanted genes or permitting genes to advance novel occupation. Genome sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The CRISPR/Cas9 gene-editing system has revolutionized research in animal and plant biology since its usage in genome editing was first demonstrated in mammalian cells in 2012 [73]. According to Rathore et al [23] first-generation CRISPR/Cas9 genome editing involves simple manipulationand cloning techniques that can be applied to a variety of guide RNAs to edit different locations in the targeted organism's genome (Figure 2). With the use of CRISPR/Cas, crop species can be precisely edited, opening the door to the generation of favorable germplasm and new, more sustainable agricultural systems.…”
Section: Clustered Regularly Interspaced Short Palindromic Repeats (C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The CRISPR/Cas9 gene-editing system has revolutionized research in animal and plant biology since its usage in genome editing was first demonstrated in mammalian cells in 2012 [73]. According to Rathore et al [23] first-generation CRISPR/Cas9 genome editing involves simple manipulationand cloning techniques that can be applied to a variety of guide RNAs to edit different locations in the targeted organism's genome (Figure 2). With the use of CRISPR/Cas, crop species can be precisely edited, opening the door to the generation of favorable germplasm and new, more sustainable agricultural systems.…”
Section: Clustered Regularly Interspaced Short Palindromic Repeats (C...mentioning
confidence: 99%
“…This is a marvelous time for genetics, due to advances in genetic analysis and genetic manipulation. Genome editing, the most recent crop-enhancement method, allows precise changes of the plant genome by deleting undesired genes or enabling genes to acquire new functions [23]. Numerous crops' genomes have been sequenced, and improvements in genome-editing techniques have made it possible to breed for desired features.…”
Section: Introductionmentioning
confidence: 99%